Performance Analysis of Supply Chain Management PT. Asia Palem Lestari uses The Supply Chain Operation Reference (SCOR) Method - Lubis, Siti Zahra Khostamaru Aspia; Rahmani, Nur Ahmadi; Harahap, Muhammad Ikhsan (PT Mattawang Mediatama Solution, 2024)
The purpose of this research is to evaluate the performance of the supply chain at PT. Asia Palem Lestari uses the Supply Chain Operations Reference (SCOR) method and analyzes the problems occurring within the company. The objective of this research is to enhance the company's performance by providing solutions to the identified problems. The research employs a quantitative approach with a descriptive method. Data collection involves interviews, observations to understand supply chain activities, and documentation to obtain secondary data from the company. The results of the supply chain performance calculation are derived from the attributes of performance in SCOR, which include Perfect Order Fulfillment (POF) 84% Order Fulfillment Cycle Time (OFCT) 30 days Cost of Goods Sold (COGS) 58% Cash to Cash Cycle Time (CTCCT) 64 days. This research uses the SCOR method to analyze supply chain performance and provide solutions to the identified problems. Therefore, this research can help improve the company's performance in a more effective and efficient manner.